Novel approach of dermatophytosis eradication in shelters: effect of Pythium oligandrum on Microsporum canis in FIV or FeLV positive cats - Martina Načeradská; Michaela Fridrichová; Martina Frühauf Kolářová; Tereza Krejčová (BMC Veterinary Research, 2021)
Abstract Background Shelters and similar facilities with a high concentration and fluctuation of animals often have problems with various infections, which are usually difficult to solve in such environments and are very expensive to treat. This study investigated the eradication of Microsporum canis, the widespread cause of zoonotic dermatophytosis in shelters, even in immunosuppressed feline leukaemia virus or feline immunodeficiency virus positive cats. Results Our study showed the increased effectiveness of an alternative topical therapy for affected animals using the mycoparasitic fungus Pythium oligandrum, which is gentler and cheaper than the standard systemic treatment with itraconazole, and which can also be easily used as a preventative treatment. A decrease in the number of M. canis colonies was observed in cats treated with a preparation containing P. oligandrum 2 weeks after the start of therapy (2 cats with P-1 score, 2 cats with P-2 score, 5 cats with P-3 score) compared with the beginning of the study (9 cats with P-3 score = massive infection). The alternative topical therapy with a preparation containing P. oligandrum was significantly more effective compared with the commonly used systemic treatment using itraconazole 5 mg/kg in a 6-week pulse. After 16 weeks of application of the alternative topical therapy, the clinical signs of dermatophytosis were eliminated throughout the whole shelter. Conclusion The complete elimination of the clinical signs of dermatophytosis in all cats indicates that this therapy will be useful for the management and prevention of zoonotic dermatophytosis in animal shelters.